The Effect Of Using SDKI And Wilkinson Book On The Accuracy Level Of Nursing Diagnosis by Poltekkes Palu Nursing Student: PENGARUH PENGGUNAAN BUKU STANDAR DIAGNOSIS KEPERAWATAN INDONESIA (SDKI) DAN DIAGNOSIS KEPERAWATAN WILKINSON EDISI 10 TERHADAP TINGKAT KETEPATAN DIAGNOSIS KEPERAWATAN MAHASISWA POLTEKKES PALU - Hasan, Sri Musriniawati; Mulyanto, Atim (Lentora Nursing Journal, 2022)
Nursing diagnosis is a clinical judgement made by a nurse about patients’ respond towards their health condition. Data shows that 40% of nursing students don’t have enough skills to make precise nursing diagnose. The aim of this study is to assess the effect of the use of the SDKI book and Wilkinson nursing diagnosis 10th edition book on the nursing students’ accuracy in making nursing diagnoses. We use a quasi-experimental method with the second grade of Poltekkes Palu nursing students as the subject of this study (n=93). The subjects were then divided into 3 groups. The first group was given the SDKI book as the intervention, the second group with the Wilkinson, and the third group was the control. Data were collected and analyzed with one-sample t-test (α<0,05) to assess the students’ nursing diagnose accuracy before and after interventions. Results show that there is a statistically significant increment before and after intervention in the Wilkinson group (α = 0,018). While there are no significant increments both in the SDKI group (9,2 point increment), Wilkinson group (42 point increment), and in the control group (10,8 point of increment). In conclusion, the use of Wilkinson nursing diagnoses 10th edition affects the increment of Poltekkes Palu students’ nursing diagnosis accuracy.